Implementasi Tahap Perkembangan Kognitif Piaget pada Penguasaan Konsep IPA Siswa Kelas VI Sekolah Dasar - Sutji Rahaju; Endang Ekowarni (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
This study was designed to investigate the stages of students’ cognitive development, the relationship between cognitive stages and students’ mastery of science concepts, the differences in science concepts among the cognitive stages, and the differences in mastery of science concepts between boys and girls. Using purposive random sampling, this study involved 115 sixth-grade students. The data were collected using tests of cognitive developmental stages and of science-concept mastery. The Pearson product moment correlations, one-way anova, and t-test were employed to analyze the data. The findings indicate that 60% of the students were at the concrete operation stages, whereas the rest were at the beginning of the formal operation stage. The study also found that there was a relationship between cognitive development and science-concept mastery, that there were differences in the mastery among cognitive developmental stages, and that there was no difference in science mastery between boys and girls.